IoT-oriented software platform applied to sensors-based farming facility with smartphone farmer app - P. Visconti; N. I. Giannoccaro; R. de Fazio; S. Strazzella; D. Cafagna (Institute of Advanced Engineering and Science, 2020)
This work describes the design of innovative IoT-oriented farm management system that employs low-cost WSN for detecting soil, environmental and crops parameters that properly processed, in combination with weather forecasts, are used to determine future farming activities based on agronomic models implemented in the software platform. Goals of carried out research activity are to guarantee production both qualitatively and quantitatively of cultivated crops, to increase company income and reduce environmental impacts; achieving these objectives is a prerequisite for implementing of sustainable agriculture. Connection between traditional cropping systems and innovative technologies is achieved through the utilization of low-cost wireless electronic modules for acquiring data from connected sensors. The fertigation system operation is supported by solar-powered low-cost WSN capable of constantly monitoring soil and environmental parameters; thanks to sensor nodes properly positioned in cultivated land or greenhouse, interest parameters of both air and soil are detected and transmitted to on-cloud database, to allow monitoring and remote control from enabled users (farmer or agronomist). For this aim, an application specifically realized and tested during the different fertigation system’s functional tests, allows users to visualize and eventually remotely intervene by using a smart-phone or tablet.